中国高等教育投资体制多元化的经济分析= Analysis of the diversity of investment mechanism of advanced education in China - 陈方 Chen, Fang (2008)
The lack of fund for high education is a commonly observed phenomenon in the world. Hence reform in the high education investment system focuses on open up of the sources of the fund. In China, due to the limited government budget and single source of government fund, the short of fund for high education is even severe. Diversification of the high education investment mechanism becomes urgent and important.